Company displacement plans: a proposal to improve mobility in the metropolitan area of Lima and Callao - Córdova-Chavez, Lucia Salome (2021)
The objective of this research is to analyze the characteristics and behaviors of the mobility to work of a group of workers in the Metropolitan Area of ​​Lima and Callao, in order to propose guidelines for the implementation of the Company Displacement Plans (PDE) as public policy to manage travel demand. Therefore, a case study applied to 168 workers distributed in 31 public and private organizations was carried out. Surveys and interviews were applied as tools to collect quantitative and qualitative information on mobility. The information processing allowed to characterize the sample and determine the travel rate that is equivalent to 3.6 trips/day (including all modes of transport and travel reasons), of which on average 1.3 trips/day are for work and 1.4 trips / day is preferably made by public transport. Based on this and other characteristics of land use and transport of workers, a set of strategies was proposed to be implemented by organizations to promote sustainable travel, such as the installation of showers and cycle parking at work to encourage the use of the bicycles, financial incentives for the use of public transport and mobile applications to practice carpooling among co-workers to optimize journeys and in part reduce them.